Analysis Of The Quality Of Population Administration And Civil Registration Services In Bareng Village, Klojen District, Malang City - supriyanto, didik (International Journal of Education, Vocational and Social Science, 2022)
This study was designed to determine and analyze the quality of public population administration services in Bareng Village, Klojen District, Malang City. This research is a type of qualitative descriptive research with data collection through interviews, observation, and literature study. The informants taken by the researchers were secretaries, employees of the Bareng Village, Klojen District, Malang City, and community recipients of services in the Together Village. In this study, researchers used the dimensions of transparency, responsiveness, assurance, empathy and direct evidence to determine the quality of population administration services in Urban village Bareng. Based on ten indicators from five dimensions, namely: Tangible, Reability, Responsiveness, Assurance, Emphaty, only a few indicators are considered lacking. These deficiencies include, among others, the absence of adequate parking areas, special rooms for smokers and people with special disabilities which affect the comfort of the community, lack of physical facilities such as benches around counters and waiting rooms and the lack of discipline of some sub-district employees. Overall, public services in Kelurahan Bareng are considered good, although there are still a number of things that need to be improved and optimized. Keywords: Keywords: quality of service, population administration, Urban village